Thrombin activatable fibrinolysis inhibitor plasma levels and TAFI Thr325Ile genetic polymorphism in a cohort of Egyptian sickle cell disease patients and impact on disease severity - Hamdy, Mona; Shaheen, Iman A.; Khallaf, Mohamed; Selim, Yasmeen M. M. (Pediatric blood & cancer, 2024)
Background Thrombin is a critical protease modulating thrombosis as well as inflammation, which are one of the main pathophysiological mechanisms in sickle vasculopathy, and its levels were reported to be high in sickle cell disease (SCD). The thrombin–thrombomodulin complex activates the TAFI inhibitor of fibrinolysis, which acts by reducing plasmin affinity for its substrate thus hindering fibrinolysis. Objective We aimed to determine the influence of the Thr325Ile single nucleotide polymorphism (SNP) on TAFI antigen levels and potential effects on the severity of SCD in a cohort of Egyptian patients. Methods Genotyping of Thr325lle polymorphism using Taq‐Man SNP genotyping assay and TAFI level measurement using an enzyme‐linked immunosorbent assay were performed for 80 SCD patients (45 homozygous HbSS, 16 S/β0 and 19 Sβ+) as well as 80 age‐ and gender‐matched healthy control subjects. Results Plasma TAFI levels were higher in SCD patients with Thr325Ile polymorphism, yet the difference was not statistically significant (p = .204). SCD patients with polymorphic genotypes had a greater number of hospital admissions (p = .03). Ten patients with acute chest syndrome had the homozygous polymorphic genotype (GG), and all patients with pulmonary hypertension had the polymorphic genotype (six were homozygous [GG] and five were heterozygous [GA]). Patients with SCD complicated with pulmonary hypertension showed significantly higher plasma TAFI levels (p = .044). Conclusion The analysis of Thr325Ile polymorphisms combined with plasma TAFI levels suggests that the analyzed SNP could influence plasma TAFL levels and SCD disease severity and hospitalization rates, which could be predictors for complex disease.